Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Effects of defatting treatments on flavor components and lipid characteristics in bowl-steamed Tan lamb: A comprehensive investigation based on lipidomics and multi-platform flavor analysis - Wen Wang; Yufeng Duan; Xue Yang; Ruheng Shen; Mengying Liu; Xiaoqin Xi; Li Zhang; Long He; Yuling Qu; Liang Lin; Qiang Cheng (Food Chemistry, 2026)

Dynamic Changes in Serum Biochemical Indices and Alternative Splicing Events Revealed Molecular Regulatory Mechanisms in Rainbow Trout Under Copper Stress - Junhao Lu; Jinqiang Quan; Jing Zhou; Yucai Pan; Jiahui Zhang; Ziguo Wang; Yuling Qu (Marine Biotechnology, 2026)

Cuproptosis is involved in small intestinal toxicity in the paraffins during pregnancy - Juan Tang; Zemin Xu; Mengna Jiang; Chao Luo; Xiaoyan Li; Yuling Jiang; Yi Qu; Jialing Ruan; Xiaoke Wang; Meihua Zheng; Wing-Cheung Law; Xinyuan Zhao (Toxicology Letters, 2025)

Target-activated DNAzyme and ion-functionalized DNA nanospheres enable dual cfDNA homogeneous electrochemical analysis for tuberculosis diagnosis - Yanming Meng; Runlian Qu; Yue Wang; Chunying Zhang; Wu Peng; Yuling Xiao; Hongxia Ruan; Hao Chen; Binwu Ying; Piaopiao Chen (Chemical Engineering Journal, 2025)

Hierarchical MXene@PBA@IL nanohybrids towards high-efficiently enhance fire safety of epoxy resin - Jirui Qu; Gaoyuan Li; Biyu Huang; Haopeng Zhang; Yuling Wang; Richeng Lian; Lei Liu; Lei Yang; Baojun Li; Xilei Chen; Chuanmei Jiao (Chemical Engineering Journal, 2025)

In-situ air bubble for efficient membrane scaling cleaning with a catalytic nanofiber membrane in membrane distillation - Zhongsen Yan; Ziyue Zhang; Yaman Huang; Haiqing Chang; Dan Qu; Yuling Jiang; Hongting Wan; Senlin Shao; Fangshu Qu (Desalination, 2025)

LINC01224 promotes the Warburg effect in gastric cancer by activating the miR-486-5p/PI3K axis - Yuling Bin; Minji Liu; Rong He; Pingfei Tang; Weiming Qu; Dajun Wu; Lin Tan; Qian Wang; Peng Jiang; Hongsai Hu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Transcriptomic analysis reveals the mechanism of ozone fumigation combined with polyethylene nanopackaging for delaying the browning and softening of mushrooms (Agaricus bisporus) - Biao Wang; Jianmin Yun; Weihong Guo; Jiawei Shen; Ting Wang; Fengyun Zhao; Yuling Qu; Liang Yao (Postharvest Biology and Technology, 2025)

Enzymatic browning of button mushrooms during postharvest cold chain circulation - Biao Wang; Ting Wang; Jianmin Yun; Yuling Qu; Xuerui Wang; Fengyun Zhao; Liang Yao (Food Bioscience, 2025)

Pre-introducing Li4NiWO6 defect phase by tungsten modification enables highly stabilized Ni-rich cathode - Fanghui Du; Hanyu Qu; Xiaoxuan Yu; Lei Ding; Pengfang Zhang; Yan Wang; Yuling Chen; Yingchao Wang; Xitong Zhang; Junwei Zheng (Chemical Engineering Journal, 2024)

Research progress of microfluidics-based food safety detection - Wenjun Jiang; Qu Tang; Yidan Zhu; Xijuan Gu; Li Wu; Yuling Qin (Food Chemistry, 2024)

A novel polyethylene nanopackaging combined with ozone fumigation delayed the browning and softening of Agaricus bisporus during postharvest storage - Biao Wang; Jianmin Yun; Chenguang Ye; Siya Xu; Weihong Guo; Fengyun Zhao; Yuling Qu; Yang Bi (Postharvest Biology and Technology, 2024)

Long-term effectiveness and sustainability of EHC remediation in carbon tetrachloride-contaminated groundwater: Mechanistic understanding and practical applications - Liu Ling; Yaqiang Wei; Haobo Niu; Hang Zhao; Yuling Chen; Dan Qu; Miao Gao; Jian Chen (Journal of Cleaner Production, 2024)

The relationship between antidepressants and breast cancer: evidence from Mendelian randomization - Dong Niu; Chenchen Li; Xiaoyu Yan; Haoran Qu; Yuling Zheng (Cancer Causes & Control, 2024)
Background The use of antidepressants has increased over the years, but the relationship between antidepressant use and the risk of breast cancer is not uniform because of confounding factors. We aimed to assess the effect of antidepressants on breast cancer risk using a two-sample Mendelian randomization (MR) approach.stet Methods Secondary data analysis was performed on pooled data from genome-wide association studies based on single-nucleotide polymorphisms that were highly correlated with antidepressants, SSRI drugs, and serotonin and prolactin levels were selected as instrumental variables to evaluate the association between antidepressants and SSRI drugs and prolactin levels with breast cancer and ER+/ER- breast cancer. We then performed a test of the hypothesis that SSRI drugs elevate prolactin concentrations. We performed two-sample Mendelian randomization analyses using inverse variance weighting, MR-Egger regression, and weighted median methods, respectively. Results There was no significant risk association between antidepressant and SSRI use and the development of breast cancer, ER-positive or ER-negative breast cancer ( P > 0.05), and serotonin concentration was not associated with breast cancer risk ( P > 0.05). There was a positive causal relationship between prolactin levels and breast cancer (IVW, P = 0.02, OR = 1.058) and ER-positive breast cancer (Weighted median, P = 0.043, OR = 1.141; IVW, P = 0.009, OR = 1.125). Results in SSRI medication and prolactin levels showed no association between SSRI analogs and prolactin levels ( P > 0.05). Conclusion Large MR analysis showed that antidepressants as well as SSRI drugs were not associated with breast cancer risk and the SSRI-prolactin-breast cancer hypothesis did not hold in our analysis.

The delaying effect of a novel polyethylene nanopackaging on postharvest stipe elongation of Flammulina velutipes and its mechanism analysis - Yuxuan Zhao; Jianmin Yun; Biao Wang; Yuling Qu; Fengyun Zhao; Yang Bi (Postharvest Biology and Technology, 2023)

Surface engineering based on element interdiffusion and interfacial reactions to boost the performance of LiCoO2 cathode material - Fanghui Du; Zhongxu Fan; Lei Ding; Yan Wang; Wenjing Shi; Jie Zhang; Hanyu Qu; Xiaoxuan Yu; Yuling Chen; Junwei Zheng (Chemical Engineering Journal, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Remediation of atrazine-contaminated soil in a fluidized-bed DBD plasma reactor - Nan Jiang; Ying Qu; Jinwei Zhu; Hongchang Wang; Ju Li; Yun Shu; Yutao Cui; Yuling Tan; Bangfa Peng; Jie Li (Chemical Engineering Journal, 2023)

Generation and Screening of T-DNA Insertion Mutants Mediated by Agrobacterium tumefaciens in the Garden Asparagus Stem Blight Pathogen Phomopsis asparagi - Yueping Zhang; Huaxiang Qu; Ping Zhao; Yongping Tang; Jingsong Zhou; Shaochun Luo; Yuling Yin; Guangyu Chen (Current Microbiology, 2017)

Calcium regulates glutamate dehydrogenase and poly-γ-glutamic acid synthesis in Bacillus natto - Yonghong Meng; Guiru Dong; Chen Zhang; Yuanyuan Ren; Yuling Qu; Weifeng Chen (Biotechnology Letters, 2016)

Erythropoietin Mediates Neurobehavioral Recovery and Neurovascular Remodeling Following Traumatic Brain Injury in Rats by Increasing Expression of Vascular Endothelial Growth Factor - Ye Xiong; Yanlu Zhang; Asim Mahmood; Yuling Meng; Changsheng Qu; Michael Chopp (Translational Stroke Research, 2011)